Noise-induced annoyance from transportation noise: Short-term responses to a single noise source in a laboratory - Kim, Jaehwan; Lim, Changwoo; Hong, Jiyoung; Lee, Soogab (The Journal of the Acoustical Society of America, 2010)
An experimental study was performed to compare the annoyances from civil-aircraft noise, military-aircraft noise, railway noise, and road-traffic noise. Two-way within-subjects designs were applied in this research. Fifty-two subjects, who were naïve listeners, were given various stimuli with varying levels through a headphone in an anechoic chamber. Regardless of the frequency weighting network, even under the same average energy level, civil-aircraft noise was the most annoying, followed by military-aircraft noise, railway noise, and road-traffic noise. In particular, penalties in the time-averaged, A -weighted sound level (TAL) of about 8, 5, and 5 dB, respectively, were found in the civil-aircraft, military-aircraft, and railway noises. The reason could be clarified through the high-frequency component and the variability in the level. When people were exposed to sounds with the same maximum A -weighted level, a railway bonus of about 3 dB was found. However, transportation noise has been evaluated by the time-averaged A -weighted level in most countries. Therefore, in the present situation, the railway bonus is not acceptable for railway vehicles with diesel-electric engines.